LITERARY TOURISM STUDIES IN FOLKLORE AT TOURIST ATTRACTIONS IN BANGKA ISLAND - Resti Amalia; Donal Fernado Lubis; Tri Arie Bowo (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study examines the role of Bangka Island’s folklore as an element of intangible cultural heritage (ICH) in shaping, promoting, and sustaining local tourist destinations. Using a descriptive qualitative approach, the research integrates semi-structured interviews, field observations, and document analysis conducted across three folklore-associated sites: Batu Rusa, Dempu Awang, and Pantai Penyusuk. Narrative mapping and thematic analysis reveal that each site presents varying degrees of narrative richness and cultural embodiment. Batu Rusa demonstrates the strongest integration of folklore into cultural practices, featuring layered narratives, rituals, and community traditions that reinforce place identity. Dempu Awang, anchored by a single hero legend, shows strong symbolic potential but limited cultural activation, while Penyusuk Beach offers a thin narrative layer overshadowed by its natural scenic appeal. The findings indicate that folklore enhances destination identity, deepens visitor engagement, and serves as cultural capital for tourism development. However, institutional utilization remains limited due to the absence of structured storytelling programs and interpretive tourism infrastructure. This study concludes that Bangka Island holds significant potential for literary and folklore-based tourism, and greater integration of ICH within tourism planning could strengthen cultural preservation and support sustainable destination development.